RESPON PERTUMBUHAN DAN PRODUKSI KACANG TANAH TERHADAP PEMBERIAN LIMBAH CAIR KELAPA SAWIT DAN PUPUK NPK - Meza, Meza; Prayoga, Gigih Ibnu; Pratama, Deni (JURNAL AGROTROPIKA, 2025)
Groundnut (Arachis hypogaea L) is the most important commodity after soybean which has a strategic role as a national food source as a source of protein and vegetable oil. The use of inorganic fertilizers must be balanced with organic fertilizers that can help improve soil properties damaged by the use of inorganic fertilizers. The goal of this study was to ascertain how NPK dosages and palm oil liquid waste interacted to influence groundnut plant development and yield. The Randomized Group Design (RAK) is the design employed in this study. The first factor is palm oil liquid waste with a dose of L1 = 100, L2 = 200, L3 = 300 ml/plant. While the second factor is NPK with a dose of P0 = 0% (without NPK fertilizer), P1 = 25% (1 gram/plant, P2 = 50% (2 grams/plant), P3 = 100% (4 grams/plant). The parameters observed were plant height, number of leaves, flowering age, number of flowers, number of filled pods, number of empty pods, weight of filled pods, weight of empty pods, wet weight of stover, dry weight of stover, weight of 100 seeds. The best treatment is the combination of 300 ml/plant of palm liquid waste and 50% (2 grams/plant) NPK (L3P3). The best treatment is 50% NPK (2 grams/plant) (P2).